Problem-Based Learning : an Approach to Medical Education. - Barrows, Howard S., 1928- (Springer series on medical education., 1980)
In this book, the authors address some basic problems in the learning of biomedical science, medicine, and the other health sciences. Students in most medical schools, especially in basic science courses, are required to memorize a large number of "facts," facts which may or may not be relevant to medical practice. Problem-based learning has two fundamental postulates--the learning through problem-solving is much more effective for creating a body of knowledge usable in the future, and that physician skills most important for patients are problem-solving skills, rather than memory sk.